Planejamento estratégico nas microempresas em Pau dos Ferros/RN - Leite, Ávilo Ferreira (Universidade Federal Rural do Semi-Árido, 2018)
Given the competitive scenario in which companies are currently included, it is of fundamental importance that they have a differential in order to remain in the market and to have a higher profitability. In this context the paper seeks to present what is the strategic planning, the types of planning and to see the results that they provide. In order to obtain the data, a questionnaire was applied in 61 microenterprises, being classified as individual microentrepreneur, microenterprise and small enterprises. In order to obtain the data, a field survey was carried out to analyze the microenterprises in the city of Pau dos Ferros / RN. in the services and trade sectors, the type of research carried out was a quantitative. In this way the questionnaires had the greater objective to identify the competitive advantages that the companies obtain by doing the strategic planning and what the difficulties for the implementation of the same, in addition, through the questions could identify other factions within the microenterprises, as for example the concern of companies in relation to their competitors, if their managers have a vision of the company in the future, another point was whether the company does the strategic planning regularly. With all this, it was possible to achieve the objective, identifying the competitive advantages and the obstacles to the implementation of strategic planning.
Keywords: Planejamento Estratégico; Vantagem Competitiva; Microempresas; Strategic Planning; Competitive Advantage; Microenterprises; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA